Impact of Bariatric Surgery on Moderate to Severe Psoriasis: A Retrospective Nationwide Registry Study - Marta Laskowski; Linus Schiöler; Johan Ottosson; Marcus Schmitt-Egenolf; Ann-Marie Wennberg; Torsten Olbers; Kjell Torén; Helena Gustafsson (Medical Journals Sweden, 2021)
Studies of the effects of bariatric surgery on psoriasis are few, with conflicting results. By linking the Swedish National Register for Systemic Treatment of Psoriasis (PsoReg) with the Scandinavian Obesity Surgery Registry (SOReg), individuals with psoriasis who had undergone bariatric surgery in Sweden during 2008 to 2018 were identified, and matched with data for patients with psoriasis in PsoReg. Psoriasis Area Severity Index (PASI) and Dermatology Life Quality Index (DLQI) were compared between the groups. Altogether, 50 operated individuals (median body mass index (BMI) 38.7 kg/m2]) and 91 non-operated individuals (median BMI 33.0 kg/m2) were included. Control of disease at baseline was good in both groups. Linear mixed models showed no significant difference in psoriasis disease burden, measured as changes in mean PASI (ΔPASI) (-1.2, p = 0.43) and DLQI (ΔDLQI) (-2.2, p = 0.34). In summary, this study demonstrated no significant effect of bariatric surgery on psoriasis disease burden in patients with relatively well-controlled moderate to severe psoriasis.